(untitled) (Fiep Bulletin - online, 2012)
PRINCE FAISAL BIN FAHAD INTERNATIONAL PRIZE FOR ARAB SPORT DEVELOPMENT RESEARCHES FIEP DELEGATES STRUCTURE OF THE FIEP FIEP EXECUTIVE BOARD 2008-2012 ABOUT THE FIEP FIEP CROSS OF HONOR SUBSCRIPTION FORM